2008
DOI: 10.1287/moor.1070.0288
|View full text |Cite
|
Sign up to set email alerts
|

An Asymptotically Optimal Policy for a Quantity-Based Network Revenue Management Problem

Abstract: We consider a canonical revenue management problem in a network setting where the goal is to find a customer admission policy to maximize the total expected revenue over a fixed finite horizon. There is a set of resources, each of which has a fixed capacity. There are several customer classes, each with an associated arrival process, price, and resource consumption vector. If a customer is accepted, it effectively removes the resources that it consumes from the system. The exact solution cannot be obtained for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 10 publications
(18 reference statements)
3
55
0
Order By: Relevance
“…For fast-moving items, applying the no-pooling policy may achieve asymptotical optimal performance. This result appears to be consistent with those found in a few of the papers in the revenue management literature (e.g., [9,25]). However, these studies have developed their analytical results without optimizing the initial inventories.…”
Section: Optimal Initial Order Quantitiessupporting
confidence: 92%
“…For fast-moving items, applying the no-pooling policy may achieve asymptotical optimal performance. This result appears to be consistent with those found in a few of the papers in the revenue management literature (e.g., [9,25]). However, these studies have developed their analytical results without optimizing the initial inventories.…”
Section: Optimal Initial Order Quantitiessupporting
confidence: 92%
“…This result is similar to that of Reiman and Wang (2008). The proof of Theorem 6.1 does contain the explicit construction of the stopping times.…”
supporting
confidence: 72%
“…conditions under which re-solving will result in a monotonic increase in revenue). Reiman and Wang (2008) showed that, with a properly chosen re-solving time, a single re-solve is enough to reduce the order of revenue loss from O(…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, [Liberman and Yechiali 1978] analyze a hotel reservation system where overbooking is allowed and the goal is to find the optimal overbooking level. [Reiman and Wang 2008] propose an admission control strategy for reservation system with different classes of customers. [Bertsimas and Shioda 2003] propose a policy for accepting/rejecting restaurant reservations.…”
Section: Related Workmentioning
confidence: 99%